A Genetically Encoded Dark-to-Bright Biosensor for Visualisation of Granzyme-Mediated Cytotoxicity - Bednar, Christopher; Kübel, Sabrina; Cordsmeier, Arne; Scholz, Brigitte; Menschikowski, Hanna; Enßer, Armin (International Journal of Molecular Sciences, 2023)
Granzyme B (GZMB) is a key enzyme released by cytotoxic T lymphocytes (CTL) and natural killer (NK) cells to induce apoptosis in target cells. We designed a novel fluorogenic biosensor which is able to assess GZMB activity in a specific and sensitive manner. This cleavage-responsive sensor for T cell activity level (CRSTAL) is based on a fluorescent protein that is only activated upon cleavage by GZMB or caspase-8. CRSTAL was tested in stable cell lines and demonstrated a strong and long-lasting fluorescence signal upon induction with GZMB. It can detect GZMB activity not only by overexpression of GZMB in target cells but also following transfer of GZMB and perforin from effector cells during cytotoxicity. This feature has significant implications for cancer immunotherapy, particularly in monitoring the efficacy of chimeric antigen receptor (CAR)-T cells. CAR-T cells are a promising therapy option for various cancer types, but monitoring their activity in vivo is challenging. The development of biosensors like CRSTAL provides a valuable tool for monitoring of CAR-T cell activity. In summary, CRSTAL is a highly sensitive biosensor that can detect GZMB activity in target cells, providing a means for evaluating the cytotoxic activity of immune cells and monitoring T cell activity in real time.
CRIS-Team Scopus Importer:2023-09-22
Keywords: CAR-T cells; fluorogenic biosensor; granzyme B; T cell cytotoxicity

Cars—a new perspective to hcmv treatment - Bednar, Christopher; Enßer, Armin (Viruses, 2021)
Human cytomegalovirus (HCMV), by primary infection or reactivation, represents a great risk for immune-suppressed or compromised patients. In immunocompetent humans, the immune system suppresses the spread of HCMV during an infection, resulting in a mostly asymptomatic or mild course of the disease, whereas in immune suppressed patients, the compromised host immune response cannot control the viral infection. Multiple viral immunomodulatory mechanisms additionally contribute to immune evasion. Use of chimeric antigen receptors (CARs), a treatment strategy adapted from cancer immunotherapy, is investigated for possible application to combat HCMV and other infections in immunocompromised patients. The administration of CAR+ T-cells directed against HCMV antigens can bypass viral immune evasion and may complement existing treatment methods. This review gives a short overview of HCMV, the obstacles of current treatment options as well as a brief introduction to CARs and the current research situation on CAR+ T-cells against HCMV.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Adoptive T-cell therapy; Antiviral immunotherapy; Chimeric antigen receptor (CAR); Cytotoxic T-lymphocytes; Human cytomegalovirus (HCMV)

Evaluation of Bispecific T-Cell Engagers Targeting Murine Cytomegalovirus - Menschikowski, Hanna; Bednar, Christopher; Kübel, Sabrina; Hermann, Manuel; Bauer, Larissa; Thomas, Marco; Cordsmeier, Arne; Enßer, Armin (Viruses, 2024)
Human cytomegalovirus is a ubiquitous herpesvirus that, while latent in most individuals, poses a great risk to immunocompromised patients. In contrast to directly acting traditional antiviral drugs, such as ganciclovir, we aim to emulate a physiological infection control using T cells. For this, we constructed several bispecific T-cell engager (BiTE) constructs targeting different viral glycoproteins of the murine cytomegalovirus and evaluated them in vitro for their efficacy. To isolate the target specific effect without viral immune evasion, we established stable reporter cell lines expressing the viral target glycoprotein B, and the glycoprotein complexes gN-gM and gH-gL, as well as nano-luciferase (nLuc). First, we evaluated binding capacities using flow cytometry and established killing assays, measuring nLuc-release upon cell lysis. All BiTE constructs proved to be functional mediators for T-cell recruitment and will allow a proof of concept for this treatment option. This might pave the way for strikingly safer immunosuppression in vulnerable patient groups.
CRIS-Team Scopus Importer:2024-07-12
Keywords: bispecific; bispecific T-cell engager; BiTE; CMV; cytomegalovirus; murine cytomegalovirus; T cell; T-cell toxicity

Re-Analysis of the Widely Used Recombinant Murine Cytomegalovirus MCMV-m157luc Derived from the Bacmid pSM3fr Confirms Its Hybrid Nature - Cordsmeier, Arne; Bednar, Christopher; Kübel, Sabrina; Bauer, Larissa; Enßer, Armin (International Journal of Molecular Sciences, 2023)
Murine cytomegalovirus (MCMV), and, in particular, recombinant virus derived from MCMV-bacmid pSM3fr, is widely used as the small animal infection model for human cytomegalovirus (HCMV). We sequenced the complete genomes of MCMV strains and recombinants for quality control. However, we noticed deviances from the deposited reference sequences of MCMV-bacmid pSM3fr. This prompted us to re-analyze pSM3fr and reannotate the reference sequence, as well as that for the commonly used MCMV-m157luc reporter virus. A correct reference sequence for this frequently used pSM3fr, containing a repaired version of m129 (MCK-2) and the luciferase gene instead of ORF m157, was constructed. The new reference also contains the original bacmid sequence, and it has a hybrid origin from MCMV strains Smith and K181.
CRIS-Team Scopus Importer:2023-10-06
Keywords: MCMV; MCMV bacmid reference; MCMV-m157lucMCK-2 repair; pSM3fr